2016
DOI: 10.1002/jcad.12097
|View full text |Cite
|
Sign up to set email alerts
|

Ethics and Relationship: From Risk Management to Relational Engagement

Abstract: In this article, the underlying assumptions of the current ACA Code of Ethics (2014a) are examined as they are embedded in historical and cultural contexts. A relational ethic situated within relational-cultural theory that provides an alternative framework for understanding ethics in a relational and compassionate way is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…T he ethical decision‐making process begins when conclusions are made subconsciously in the human brain (Drumwright, Prentice, & Biasucci, ), and when the conclusions reach conscious perception, the process immediately shifts to the use of “cognitive shortcuts” to solve the dilemma with the least amount of effort (McMahon & Good, ). Additionally, personal dispositions and characteristics can easily dominate an individual's ethical decision‐making, thereby diminishing the impact of ethics codes, laws, and ethical decision‐making models (Birrell & Bruns, ; Fialkov, Jackson, & Rabinowitz, ). Using personal morals and values (Kitchener, ), as well as consultation with peers (Tenbrunsel & Chugh, ), does not guarantee acceptable ethical decision‐making.…”
mentioning
confidence: 99%
“…T he ethical decision‐making process begins when conclusions are made subconsciously in the human brain (Drumwright, Prentice, & Biasucci, ), and when the conclusions reach conscious perception, the process immediately shifts to the use of “cognitive shortcuts” to solve the dilemma with the least amount of effort (McMahon & Good, ). Additionally, personal dispositions and characteristics can easily dominate an individual's ethical decision‐making, thereby diminishing the impact of ethics codes, laws, and ethical decision‐making models (Birrell & Bruns, ; Fialkov, Jackson, & Rabinowitz, ). Using personal morals and values (Kitchener, ), as well as consultation with peers (Tenbrunsel & Chugh, ), does not guarantee acceptable ethical decision‐making.…”
mentioning
confidence: 99%
“…Once ethical decision‐making reaches consciousness, McMahon and Good () found that humans use “cognitive shortcuts” when engaged in ethical decision‐making. Additionally, personal dispositions and characteristics can prevail over ethics codes, laws, and ethical decision‐making models (Birrell & Bruns, ; Fialkov, Jackson, & Rabinowitz, ). Using personal morals and values as ethical guidelines may not result in defensible ethical choices for boundary‐crossing decision‐making (Kitchener, ).…”
mentioning
confidence: 99%
“…Kitchener's () five moral principles, the ACA Code of Ethics (American Counseling Association [ACA], ), and Gottlieb's () decision‐making model are core counseling ethical information resources used by independently licensed counselors when navigating boundary‐crossing issues. Kitchener's five moral principles provide the foundation for the ACA Code of Ethics (Birrell & Bruns, ; Forester‐Miller & Davis, ) and are commonly taught in master's‐level counselor education classes to help counselors navigate ethical concerns, including boundary‐crossing issues (Granello & Young, ; Sangganjanavanich & Reynolds, ; Sheperis & Sheperis, ). So that professionals do no harm, benefit others, are fair, respect autonomy, and act faithfully to all individuals affected by the professional relationship, Kitchener suggested the use of the five moral principles when considering boundary crossings.…”
mentioning
confidence: 99%
“…Personal characteristics influence ethical decision making. If unchecked, these personal temperaments can replace ethical codes, laws, and ethical decision-making models (Birrell & Bruns, 2016;Fialkov, Jackson, & Rabinowitz, 2014). Counting on self-established ethical guidelines to guide boundary-crossing decision making is problematic because moral intuition may not result in tenable ethical choices (Kitchener, 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation